Teachers’ Engagement with Educational Research: Toward a Conceptual Framework for Locally-Based Interpretive Communities - Anwaruddin, Sardar M. (Education Policy Analysis Archives, 2015)
In this article, I re-visit the gap between educational research and practice, by reviewing some initiatives that have been taken to bridge the gap. I argue that most of these initiatives do not pay due attention to local contexts of research use. They tend to focus more on the management of researchers’ theoretical knowledge than on the generation of teachers’ pedagogical knowledge. For the development of meaningful pedagogical knowledge, I recommend that teachers be provided with appropriate opportunities to engage directly with educational research. However, I note that such engagement with research is not without challenges and constraints. Borrowing from Denzin and Lincoln (2005), I discuss three challenges—of representation, legitimation, and praxis—to teachers’ engagement with research. To overcome these challenges, I propose that teachers work as locally-based interpretive communities, in which they negotiate a communicative validity of research findings through dialogue with one another.